Peran Komunikasi dan Sikap Caring Perawat pada Tingkat Kepuasan Pasien dalam Penanganan Kegawatdaruratan - Agus Marjidin; Weslei Daeli; Bambang Suryadi; Bram Burmanajaya (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
The high volume of patient visits to the ER, both by emergency and non-emergency patients, is the main cause of crowding in the ER which can cause patient dissatisfaction. So that communication and caring attitudes of nurses are needed to overcome this condition. Patient satisfaction is the main indicator of the standard of a health facility, while communication and caring attitudes of health workers will also have an impact on patient satisfaction. The purpose of this study was to determine whether or not there is a relationship between communication and caring attitudes of nurses with the level of patient satisfaction in emergency handling in the ER of Bogor City Hospital. The descriptive analytical research method with a cross-sectional approach, the sample in this study amounted to 67 patients in the yellow zone in the ER of Bogor City Hospital. The results of the study showed good communication as many as 62 respondents (92.5%). The caring attitude of nurses who carried out caring was 54 respondents (80.6%) and patients who were satisfied were 63 respondents (94%). By using the Chi-Square analysis test, the P value = 0.025 on communication with the level of patient satisfaction, the P value = 0.021 of the nurse's caring attitude with the level of patient satisfaction. The conclusion of this study is that there is a relationship between communication and caring attitudes of nurses with the level of patient satisfaction. The better the communication and caring attitudes of nurses, the better the impact on patient satisfaction in emergency services.